THE EFFECT OF MANGO LEAVES EXTRACT VAR ARUM MANIS (Mangifera indica L.) AS IMUNOSTIMULANTS ON MICE MODEL - Ifmaily Ifmaily; Putri Rizki Fitriani (Jurnal Inovasi Penelitian, 2021)
Background : Every time our body is always exposed to microorganisms that can cause infection. Usually we are immune to infection because of the immune system that protects us, but when the body is exposed to antigens while the immune system activity decreases, then we need immunostimulants. One of traditional plant always get to use as the traditional drug is mango plant, Previous research it have effect as antioxidant, antidiabetes type II, antiinflammatory, anticancer, antihypertensive, and antimicrobial. It contains the flavonoid, alkaloid, phenolic,and steroid compounds. This study aims to determine the effect of mango leaves extract var arum manis against the activity and phagocytosis capacity of macrophage cells, and the percentage of leukocyte cell types, as well as the effect of dose variations on the administration of var arum manis mango leaves extract. Methods :Twenty mice were divided into 4 groups. Consisting of group I getting 0.5% Na.CMC, groups II, III and IV getting mango leaves extract var arum manis with consecutive doses of 30 mg / kgBW, 60 mg / kgBW, and 120 mg / kgBW which were given respectively. orally once a day for 7 days. On the eighth day, Staphylococcus aureus bacteria were injected intraperitoneally and after one hour, the activity and capacity of macrophage cell phagocytosis and the percentage of leukocyte cell types were calculated. Result and Discussion: The activity and phagocytosis capacity of macrophage cell was determined by calculating the phagocytosis index where the results obtained were the higher the dose, the increased activity and phagocytosis capacity of macrophage cell which affected the percentage of leukocyte cell types. The data were then processed by statistical analysis of one-way ANOVA. Conclusion of research showed that the mango leaves extract var arum manis at a dose of 30 mg / KgBW, 60 mg / KgBW, 120 mg / KgBW was significant (p ≤ 0.05) and affected activity and phagocytosis capacity of macrophage cells and the percentage of leukocyte cell types significantly (p ≤ 0.05), where the most effective result was a dose of 120 mg / KgBW